1991
DOI: 10.2337/diacare.14.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Low-Glycemic Index Foods Improve Long-Term Glycemic Control in NIDDM

Abstract: A low-GI diet gives a modest improvement in long-term glycemic control but not plasma lipids in normolipidemic well-controlled subjects with NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
157
2
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(170 citation statements)
references
References 13 publications
5
157
2
3
Order By: Relevance
“…One of the major reasons for the difference between the diets that did lower day long glucose levels and the diet used in our study was the presence of legumes in the apparently more effective diets, so the simple selection of lower GI foods such as pasta and whole grain bread may not provide the expected bene®t. Changes in blood cholesterol and triglyceride occurred in a minority of studies only and our study is compatible with the second largest study of Brand et al, 1991 in which no changes were seen.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One of the major reasons for the difference between the diets that did lower day long glucose levels and the diet used in our study was the presence of legumes in the apparently more effective diets, so the simple selection of lower GI foods such as pasta and whole grain bread may not provide the expected bene®t. Changes in blood cholesterol and triglyceride occurred in a minority of studies only and our study is compatible with the second largest study of Brand et al, 1991 in which no changes were seen.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore this study is the largest so far and the reduction in GI of 20 units is comparable to the other studies and greater than that seen in the study of Brand et al (1991) which was one of the more successful studies. A reduction in fasting glucose is usually not seen and the most common observation is a reduction in day long glucose or integrated measures of glucose level such as HbAlc, glycated albumin or fructosamine one of which was seen in ®ve of the six studies.…”
Section: Discussionsupporting
confidence: 74%
“…Hence, a diet with a low glycaemic index may help prevent NIDDM. Cross-over studies in NIDDM patients have shown that decreasing dietary GI leads to improved glycaemic control (Wolever et al, 1992;Brand et al, 1991), similar to that achieved by hypoglycaemic drugs.…”
Section: Introductionmentioning
confidence: 90%
“…On the other hand, Jenkins proposed the glycemic index (GI) as a physiologic basis for qualitative classification of carbohydrate-containing foods, where low GI foods produce less glycemia than high GI foods (Jenkins et al, 1981). Since then, many metabolic studies showed that a low GI diet improves overall blood glucose and lipid profiles in normal subjects (Jenkins et al, 1987a), and patients with hyperlipidemia (Jenkins et al, 1985(Jenkins et al, ,1987b or diabetes (Jenkins et al, 1988;Brand et al, 1991;Wolever et al, 1992a, b;Jarvi et al, 1999;Luscombe et al, 1999). The GI values of 565 foods were compiled to form the international GI table in 1995.…”
Section: Introductionmentioning
confidence: 99%